Peningkatan Pengetahuan dan Keterampilan Menyikat Gigi Anak Berkebutuhan Khusus dengan Media Video - Nurmawi, Yesi; Sukarsih, Sukarsih; Asio, Asio (Pusat Penelitian dan Pengabdian kepada Masyarakat, Politeknik Kesehatatan Kemenkes Palembang, 2024)
In 2023, the Indonesian Health Survey indicated that Jambi Province has 76.9% of residents brushing their teeth daily, but only 3.8% follow the recommended routine of brushing after breakfast and before bedtime. Among children aged 10-14, 75.7% brush daily, with only 5.3% adhering to the recommended timing. This highlights a lack of knowledge about oral health in Jambi. To address this, a community service initiative was conducted at SLBN Muaro Jambi for children with special needs, using video media to educate on proper tooth brushing techniques. This effort, part of the Community Partnership Program, involved 70 children and aimed at promoting dental health. Following the education, there was a significant improvement in tooth brushing skills: from 16% to 70% in the high criteria category. This initiative successfully enhanced the knowledge and skills of children with special needs regarding oral hygiene.